1992
DOI: 10.1161/01.str.23.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler assessment of cerebral flow velocity during cognitive tasks.

Abstract: Background and Purpose: The purpose of this study was to assess the ability of transcranial Doppler ultrasonography to detect selective circulatory changes during cognitive activity.Methods: We measured cerebral artery flow velocity in 21 normal volunteers by transcranial Doppler ultrasonography during rest followed by cerebral activation. Mean and peak systolic flow velocities of the anterior, middle, and posterior cerebral arteries were measured during the performance of a commercial video game. We also meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
4
2

Year Published

1994
1994
2011
2011

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 38 publications
5
46
4
2
Order By: Relevance
“…Cerebral lateralization could be studied using TCD (Bulla-Hellweg, Vollmer, Gö tzen, Skreczek, & Hartje, 1996;Cupini et al, 1996;Droste, Harders, & Rastogi, 1989;Evers, Dannert, Rodding, Rotter, & Ringelstein, 1999;Hartje, Ringelstein, Kistinger, Fabianek, & Willmes, 1994;Kelley et al, 1992;Markus & Boland, 1992;Njemanze, 1991Njemanze, , 1996Njemanze, , 2002Njemanze, , 2004Njemanze, Gomez, & Horenstein, 1992;Rihs, Gutbrod, Steiger, Sturzenegger, & Mattle, 1995;Silvestrini, Troisi, Matteis, Razzano, & Caltagirone, 1994;Varnadore, Roberts, & McKinney, 1997;Vingerhoets & Stroobant, 1999). Studies with TCD have been cross-validated by functional MRI (Schmidt et al, 1999), and reproducibility assessed (Knecht et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral lateralization could be studied using TCD (Bulla-Hellweg, Vollmer, Gö tzen, Skreczek, & Hartje, 1996;Cupini et al, 1996;Droste, Harders, & Rastogi, 1989;Evers, Dannert, Rodding, Rotter, & Ringelstein, 1999;Hartje, Ringelstein, Kistinger, Fabianek, & Willmes, 1994;Kelley et al, 1992;Markus & Boland, 1992;Njemanze, 1991Njemanze, , 1996Njemanze, , 2002Njemanze, , 2004Njemanze, Gomez, & Horenstein, 1992;Rihs, Gutbrod, Steiger, Sturzenegger, & Mattle, 1995;Silvestrini, Troisi, Matteis, Razzano, & Caltagirone, 1994;Varnadore, Roberts, & McKinney, 1997;Vingerhoets & Stroobant, 1999). Studies with TCD have been cross-validated by functional MRI (Schmidt et al, 1999), and reproducibility assessed (Knecht et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The most similar study can be found in a research from Kelley et al [175], who analyzed brain activity using TCD while participants played a commercial video game using a joystick. Although a video game is not VR, at least it has some of the characteristics that VEs have, mainly, the engagement and the interaction with a computer generated world.…”
Section: Video Gamesmentioning
confidence: 90%
“…These values are then compared to check if there are significant differences between them. This analysis has been used in some of the previous studies [175,163,182,35].…”
Section: One Execution Of the Experimental Taskmentioning
confidence: 99%
See 2 more Smart Citations